Photobacterium damselae subsp damselae, an Emerging Fish Pathogen in the Black Sea: Evidence of a Multiclonal Origin - Terceti, Mateus S.; Öğüt, Hamdi; Osorio, Carlos R. (Amer Soc Microbiology, 2016)
Photobacterium damselae subsp. damselae is considered to be an emerging pathogen of marine fish of importance in aquaculture, with a notable increase in its geographical distribution during the last several years. In this study, we carried out for the first time to our knowledge a genetic and pathobiological characterization of 14 strains isolated from sea bass (Dicentrarchus labrax) reared in the Southeastern Black Sea, where high mortalities were observed at two aquaculture farms during the summer and autumn of 2011. Heterogeneity was evidenced among strains in phenotypical traits, such as sucrose fermentation, motility, and hemolysis. Although 11 of 14 isolates were hemolytic, we found that all of the isolates lacked the pPHDD1 virulence plasmid that encodes the phospholipase-D damselysin (Dly) and the pore-forming toxin PhlyP, two hemolysins previously reported to constitute major virulence factors for turbot. Subsequent PCR and sequencing analyses demonstrated that the 11 hemolytic isolates harbored a complete hlyA(ch) gene, a chromosome I-borne gene that encodes HlyA(ch) hemolysin, whereas the three nonhemolytic isolates contained hlyA(ch) pseudogenes caused by insertion sequence elements. Virulence challenges with two representative strains revealed that, albeit less virulent than the pPHDD1-harboring strain RM-71, the plasmidless hlyA(ch)-positive and hlyA(ch)-negative Black Sea isolates were pathogenic for sea bass. A phylogenetic analysis based on the toxR gene sequence uncovered a greater diversity in the isolates, indicating that the presence of this pathogen in the Black Sea was not caused by the introduction and spread of a single virulent clone but by the proliferation of different clones.
Keywords: [No Keywords]